OP0078 Apremilast, an Oral Phosphodiesterase 4 Inhibitor, is Associated with Long-Term (52-WEEK) Improvement in Measures of Disease Activity in Patients with Psoriatic Arthritis: Results from 3 Phase 3, Randomized, Controlled Trials. (10th June 2014) - Kavanaugh, A.; Cutolo, M.; Mease, P.; Gladman, D.; Adebajo, A.; Gomez-Reino, J.; Wollenhaupt, J.; Schett, G.; Lespessailles, E.; Hu, C.; Stevens, R.; Edwards, C.; et al.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to regulate inflammatory mediators. The PALACE 1, 2, and 3 trials compared the efficacy and safety of APR with placebo (PBO) in patients with active psoriatic arthritis (PsA) despite prior conventional disease-modifying antirheumatic drugs (DMARDs) and/or biologics. Objectives: Evaluate the impact of APR over 52 weeks on PsA disease activity. Methods: Patients were randomized 1:1:1 to receive PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline DMARD use (yes/no). Patients with <20% reduction from baseline in swollen or tender joint counts at Week 16 were required to be re-randomized to APR20 or APR30 if initially randomized to PBO, or continued on their initial APR dose. At Week 24, all remaining PBO patients were re-randomized to APR20 or APR30. This analysis reports data over 52 weeks. Disease activity was evaluated using the DAS-28 (CRP), modified PsARC response, and good or moderate EULAR response. Results: At Week 16, a significantly greater proportion of patients treated with APR achieved a modified ACR20 response vs PBO (primary endpoint). In patients initially randomized to APR and completing 52 weeks, ACR20 response was sustained over 52 weeks. APR20 and APR30 demonstrated improvement in disease activity vs PBO at Week 16, as measured by the DAS-28 (CRP), modified PsARC response, and good or moderate EULAR response. Among patients who were continuously treated with APR through 52 weeks sustained improvements were observed at Week 52 (Table). The most common adverse events reported during the PBO-controlled period (PAL 1-3; pooled) were diarrhea (12.2%), nausea (10.1%), and headache (8.0%). The safety profile of APR through 52 weeks was similar to that observed with APR for up to 24 weeks of treatment (PBO-controlled period). Conclusions: APR demonstrated clinically meaningful improvements in measures of PsA disease activity through Week 52. APR demonstrated an acceptable safety profile and was generally well tolerated through 52 weeks. Disclosure of Interest: A. Kavanaugh Grant/research support: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc., Roche, and UCB, M. Cutolo Grant/research support: Actelion, Bristol-Myers Squibb, and Sanofi-Aventis, Consultant for: Actelion, Bristol-Myers Squibb, and Sanofi-Aventis, P. Mease Grant/research support: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genetech, Janssen, Eli Lilly, Pfizer Inc., Celgene Corporation, Novartis, Roche and UCB, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genetech, Janssen, Eli Lilly, Pfizer Inc., Celgene Corporation, Novartis, Roche and UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genetech, Janssen, Eli Lilly, Pfizer Inc., and UCB, D. Gladman Grant/research support: AbbVie, Amgen, Bristol-Myers Squibb, Celgene corporation, Janssen, Pfizer Inc., Novartis and UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene corporation, Janssen, Pfizer Inc., Novartis and UCB, A. Adebajo: None declared, J. Gomez-Reino Grant/research support: Roche and Schering Plough, Consultant for: Bristol-Myers Squibb, Pfizer Inc., Roche, Schering Plough, and UCB SA, Speakers bureau: Bristol-Myers Squibb, Roche, Schering Plough, and Wyeth, J. Wollenhaupt Grant/research support: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc., and UCB, Consultant for: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc., and UCB, G. Schett Grant/research support: Abbott, Celgene Corporation, Roche, and UCB, Consultant for: Abbott, Celgene Corporation, Roche, and UCB, E. Lespessailles Grant/research support: Amgen, Eli Lilly, Novartis, and Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, and Servier, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, C. Edwards Grant/research support: Celgene Corporation, Pfizer Inc., Roche, and Samsung, Consultant for: Celgene Corporation, Pfizer Inc., Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc., and Roche, C. Birbara Grant/research support: Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, and Pfizer Inc. DOI: 10.1136/annrheumdis-2014-eular.1827